The conquest of Roman Africa by the Vandals (429-439 AD) - Le Bohec, Yann (Gerión. Revista de Historia Antigua, 2018)
Under the threat of the Goths, who arrived from Gaul, and feeling that Africa was attractive, because of its wealth, the Vandals crossed over the strait of Gibraltar. Arrived on this land, they fought victoriously in a first battle, but they met some difficulties during the siege of Hippo Regius. Then, they were again victorious on land. Finally, they entered in Carthage, by treason.
Keywords: Battle; Carthage; Hippo Regius; Strategy; Tactics; Siege.